Comparative genomics of 26 complete circular genomes of 18 different serotypes of Actinobacillus pleuropneumoniae. Issue 2 (23rd February 2022) - Donà, Valentina; Ramette, Alban; Perreten, Vincent
Abstract : Actinobacillus pleuropneumoniae is a Gram-negative, rod-shaped bacterium of the family Pasteurellaceae causing pig pleuropneumonia associated with great economic losses worldwide. Nineteen serotypes with distinctive lipopolysaccharide (LPS) and capsular (CPS) compositions have been described so far, yet complete circular genomes are publicly available only for the reference strains of serotypes 1, 4 and 5b, and for field strains of serotypes 1, 3, 7 and 8. We aimed to complete this picture by sequencing the reference strains of 17 different serotypes with the MinION sequencer (Oxford Nanopore Technologies, ONT) and on an Illumina HiSeq (Illumina) platform. We also included two field isolates of serotypes 2 and 3 that were PacBio- and MinION-sequenced, respectively. Genome assemblies were performed following two different strategies, i.e. PacBio- or ONT-only de novo assemblies polished with Illumina reads or a hybrid assembly by directly combining ONT and Illumina reads. Both methods proved successful in obtaining accurate circular genomes with comparable qualities. blast -based genome comparisons and core-genome phylogeny based on core genes, SNP typing and multi-locus sequence typing (cgMLST) of the 26 circular genomes indicated well-conserved genomes across the 18 different serotypes, differing mainly in phage insertions, and CPS, LPS and RTX-toxin clusters, which, consistently, encode serotype-specific antigens. We also identified small antibiotic resistance plasmids, and complete subtype I-F and subtype II-C CRISPR-Cas systems. Of note, highly similar clusters encoding all those serotype-specific traits were also found in other pathogenic and commensal Actinobacillus species. Taken together with the presence of transposable elements surrounding these loci, we speculate a dynamic intra- and interspecies exchange of such virulence-related factors by horizontal gene transfer. In conclusion, our comprehensive genomics analysis provides useful information for diagnostic test and vaccine development, but also for whole-genome-based epidemiological studies, as well as for the surveillance of the evolution of antibiotic resistance and virulence genes in A. pleuropneumoniae .